Eksplorasi Pendekatan Restorative Justice sebagai Mekanisme Pengurangan Angka Residivisme: Analisis Kritis terhadap Efektivitas Teori Relatif dalam Sistem Peradilan Pidana Indonesia - Nabila Maulidiya; Indi Ulya Kamalin; Jelita Yupitasari (Progressive Law Review, 2025)
Indonesia’s criminal justice system faces significant challenges related to rising recidivism rates. Data from the Directorate General of Corrections suggests that Indonesia's recidivism rate could reach 24% by 2023, indicating the limitations of conventional sentencing approaches. This research critically analyses the effectiveness of relative punishment theory and explores restorative justice as a potential alternative to reduce recidivism. Using a literature review methodology, this research examines empirical data, theoretical frameworks, and implementation challenges of restorative justice in the Indonesian legal context. Comparative analysis shows that restorative justice approaches have a significantly lower recidivism rate of 12.7%, compared to 37.8% for punitive approaches and 28.4% for rehabilitation-based approaches. The research identified key implementation factors, including law enforcement commitment, active community participation, comprehensive policy support, and effective rehabilitation programs. Structural and cultural barriers were also examined, with recommendations for adapting restorative justice to the Indonesian socio-cultural context. The study concludes that integrating restorative justice principles into the criminal justice system is a strategic approach to address recidivism.